Adiponectin Concentrations: A Genome-wide Association Study - Jee, Sun Ha; Sull, Jae Woong; Lee, Jong-Eun; Shin, Chol; Park, Jongkeun; Kimm, Heejin; Cho, Eun-Young; Shin, Eun-Soon; Yun, Ji Eun; Park, Ji Wan; Kim, Sang Yeun; Lee, Sun Ju; et al. (American journal of human genetics, 2010)
Adiponectin is associated with obesity and insulin resistance. To date, there has been no genome-wide association study (GWAS) of adiponectin levels in Asians. Here we present a GWAS of a cohort of Korean volunteers. A total of 4,001 subjects were genotyped by using a genome-wide marker panel in a two-stage design (979 subjects initially and 3,022 in a second stage). Another 2,304 subjects were used for follow-up replication studies with selected markers. In the discovery phase, the top SNP associated with mean log adiponectin was rs3865188 in CDH13 on chromosome 16 (p = 1.69 × 10−15 in the initial sample, p = 6.58 × 10−39 in the second genome-wide sample, and p = 2.12 × 10−32 in the replication sample). The meta-analysis p value for rs3865188 in all 6,305 individuals was 2.82 × 10−83. The association of rs3865188 with high-molecular-weight adiponectin (p = 7.36 × 10−58) was even stronger in the third sample. A reporter assay that evaluated the effects of a CDH13 promoter SNP in complete linkage disequilibrium with rs3865188 revealed that the major allele increased expression 2.2-fold. This study clearly shows that genetic variants in CDH13 influence adiponectin levels in Korean adults.